PENINGKATAN WAWASAN PEMASARAN DIGITAL KELOMPOK USAHA ECOPRINT DI KALIDAMI SURABAYA - Andajani, Erna; Soesanti, Arum; Tjiptawan, Ardeliah; Simangunsong, Tuani Lidiawati; Nugroho, Graviella Angelique Aretha; Paulus, Ivan Jonston; Yohanes, Marco Antonio Jose; Kurniawan, Albert Ray; Wijaya, Vegasanti (Universitas Mataram, 2024)
Ecoprint is a form of skill that prioritizes environmentally friendly products. The basic fabric materials used contain natural fibers and natural materials such as leaves, twigs and flowers to provide motifs and coloring. The Kalidami business group in Surabaya has the skills to produce ecoprints and make these ecoprint products to improve family welfare. So far, ecoprint product marketing has been carried out traditionally (offline) such as through exhibitions and bazaars, while digital marketing is still poorly understood by the Kalidami ecoprint business group. The purpose of this research related to Community Service activities is to provide knowledge and skills to the ecoprint business group in Kalidami about the use of digital marketing. Digital marketing supports traditional marketing that is already running. The method of this community service activity is carried out by presenting digital marketing materials and practices. This training activity is carried out offline. This activity is carried out in 2 meetings on different days. The participants of the activity are an ecoprint business group consisting of 5 people with the profession of housewives. The stages of implementing this activity consist of preparation, implementation and evaluation. The results of this community service activity show that the knowledge of the ecoprint business group in using digital media has increased. This can be seen from the average pre-test and post-test scores which increased by 50%. The ecoprint business group was provided with digital marketing concepts and practices. Practical activities or digital marketing skills include creating Instagram and Shopee accounts, creating content on social media with short videos or photos. Ecoprint business groups learn to edit, create video captions and upload videos or photos on social media. Ecoprint business groups provide input to the community service team as a form of evaluation and learning for the next program. The conclusion shows that the ecoprint business group has gained insight into knowledge and direct practice about online marketing. It is hoped that this activity can optimize the sale of ecoprint products in the online market.